Multimodal Analysis of Man/Husband and Woman/Wife Representations in Two Indonesian Seasoning Television Commercials - Shania Permata Chandra; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2022)
Television occupies widespread popularity and is the best and most effective medium for commercials. With the rapid business growth, television commercial (TVC) has been more and more creatively made. TVC producers usually use semiotic resources to represent a certain character. Through this study, we aim to discover the way the man/husband and woman/wife characters are represented in Royco’s The Best Gift is Homemade TVC and Kecap ABC’s Kecap ABC Bantu Suami Sejati Hargai Istri TVC using visual, gestural, and linguistic modes, and whether the representations challenge or support the traditional roles of man/husband and woman/wife and the reason using traditional gender role theory. Our findings show that, in both TVCs, the man/husband and woman/wife are represented modern roles of man/husband and woman/wife. By doing so, the TVCs persuade the target audience, regardless of their roles as man/husband or woman/wife, to cook with Royco and Kecap ABC.Keywords: Multimodality, Representations, Television Commercial (TVC)